Application of normative frameworks for assessing availability of socio-economic policies based on maqasid al shari’a principles in Muslim countries: A proposal / Mustapha Abubakar and Kabiru Jinjiri Ringim - Abubakar, Mustapha; Ringim, Kabiru Jinjiri (Universiti Teknologi MARA Selangor, 2018)
The objective of this paper is to propose a framework that will assess the availability of maqasid al shari’a based socio-economic policies in Muslim countries, and whose nebulous institutions are perturbed by the statistic that 504 million people are living in multi-dimensional poverty, suffering from range of deprivations in forty-three member countries of the Islamic Development Bank (IDB). Lack of or weak access to adequate resources remain the primary issues faced by many nations. In the midst of this though, there is a recurring argument that the level of socio economic development of human well-being must be improved. To understand development challenges of socio-economic framing in the current Muslim world, factors such as education, health, spirituality, lives and property, economy, food security as well as youth employment as based on maqasid al shari’ah framework model merit consideration. Accordingly, this paper seeks to address the gap in the current literature by incorporating education and youth unemployment factors into the socio-economic development model which is based on maqasid al sharia’h framework. The study adapted the principles of Islamic divine law that ensures an inclusive socio-economic development policy devoid of tribal, ethnic or religious sentiments. The study offered recommendations for further research on maqasid al sharia’ah applications on the socio-economic development of both Muslim and Muslim-minority countries.